Identification and validation of a gap junction protein related signature for predicting the prognosis of renal clear cell carcinoma - Huang, Yongsheng; Guo, Wenyi; Zeng, Yuan; Wang, Xinrong; Fan, Bohao; Zhang, Ying; Yan, Lei; Gu, Gangli; Liu, Zhao (Frontiers in Oncology, 2024)
Gap junction proteins (GJPs) related to cell communication and tumor development were studied to identify prognostic signatures (GRPS) associated with clear cell renal cell carcinoma (ccRCC). GJP microarray data and RNA sequencing data from tumor and paired normal tissues were obtained from GEO and TCGA databases, respectively. TCGA used LASSO and Cox regression models to identify GJPs with independent prognostic effects in ccRCC patients. Risk scores (RS) were calculated based on GRPS expression and regression coefficient to construct an RS prognostic model predicting survival. Analyses of overall survival (OS), progression-free survival (PFS), gene pan-cancer, single gene survival, gene joint effect, functional enrichment, tumor microenvironment (TME), tumor mutational burden (TMB), and drug sensitivity were conducted to explore the biological function, mechanism of action, and clinical significance of GRPS in ccRCC. GJA5 and GJB1, GRPS markers in ccRCC patients, were identified through LASSO and Cox regression models. Low GJA5 and GJB1 expression is associated with poor patient prognosis. High-RS patients had shorter OS and PFS compared to low-RS patients (p < 0.001). The risk of death for high-RS individuals was 1.695 times greater than that for low-RS individuals (HR = 1.695, 95%CI = 1.439-1.996, p < 0.001). The RS prognostic model demonstrated strong predictive power with ROC curve AUC values for 1-year, 3-year, and 5-year survival rates of 0.740, 0.781, and 0.771, respectively. The clinical column chart also predicted survival rates with AUC values of 0.859, 0.846, and 0.796 for 1-year, 3-year, and 5-year survival predictions, respectively. GRPS was associated with immune cell infiltration, TME, TMB, and chemotherapy drug sensitivity. In vitro experiments showed that GJA5 or GJB1 knockdown promoted ccRCC cell proliferation, migration, EMT, and inhibited apoptosis. GJA5 and GJB1 could be potential biological markers for predicting ccRCC survival.